Effects of Innovation Advancement on Technological Progress and Economic Growth in Uganda: A Generalized Least Squares Method - Jimmy, Alani; Bruno, Yawe; John, Mutenyo
The paper examines the long run effects of innovation advancement on technological progress and economic growth in Uganda during the 1970 to 2020 period. The paper is unique because it measures annual innovation as a ratio of level of technology to the total productivity of labor and capital. Meanwhile, it measures annual level of technology as a ratio of output to total factor. Thus, the paper demonstrates that innovation is characterized by a creative destruction problem. In the study, data sets were collected from the United Nations Database and data analyses were conducted by using the generalized least squares (GLS) method and the philosophical principle of causality. The study finds that innovation advancement as well as innovation acceleration had positive and significant effects on technological progress and economic growth in Uganda during the given period. Hence, findings in the paper support the innovation-based growth hypothesis that there is a positive linkage between innovation and economic growth. The paper also finds that during the given period innovation gave rise to technological advancement in Uganda. This research work attempts to aid policy makers, educators and financers in Uganda to stimulate innovation advancement, technological progress and economic growth in the country.